Leukemia - Li, Weijie (Exon Publications, 2022)
Leukemia, the most common cancer in children, is a hematological malignancy caused by clonal proliferation of abnormal lymphoid or hematopoietic cells in the bone marrow and/or lymphoid system. Leukemias can be classified into many subtypes based on cell of origin, clinical, phenotypic, and genetic information. Tremendous advances have been made in the leukemia field during the last several decades. Our understanding of the biology of different types of leukemia has significantly improved through a huge amount of basic and clinical research. The application of advanced diagnostic technologies has led to the identification of not only new leukemia subtypes but also the clinical outcomes of all leukemias. One classic example is pediatric acute lymphoblast leukemia, the most common fatal disease in children, which has become a highly curable disease with a curable rate of over 80%. The book Leukemia, written by an international team has covered many of these achievements. It provides the most up-to-date information on important topics such as the new 5th Edition of the World Health Organization Classification of hematolymphoid tumors, prognostic and predictive biomarkers, minimal residual disease, pharmacogenomics, diagnostic use of flow cytometry, and gives updates on several interesting leukemia entities such as infant leukemia, hairy cell leukemia, acute myeloid leukemia with myelodysplasia-related changes, secondary acute myeloid leukemia, and myeloid/lymphoid neoplasms with PDGFRA rearrangement. This book will be of great value to a wide audience seeking information in the leukemia field either for clinical purposes or research purposes.